(untitled) (Global Journal of Science Frontier Research, 2016)
This study was conducted to determine the possibility of blending selected sweet potato flour to wheat flour to produce breads and to evaluate nutritional, anti-nutritional factors, quality and sensory attributes of breads. Because of its potential source of nutrients compared to yellow and white sweet potato varieties, orange sweet potato cultivar was selected for bread making and six blending ratios of its flour with wheat flour (0:100, 5:95, 10:90, 15:85, 20:80 and 25:75) were designed. Functional properties of composite flour such as wet gluten and water absorption capacity was decreased and, increased respectively as blending ratio of sweet potato flour increases. Quality parameters of breads such as loaf size (volume, specific volume and height) were significantly decreased but loaf weight was increased as blending ratio of sweet potato flour increases.